Romaine Lacaux - Pierre-Auguste Renoir (Wikimedia Commons, 1864)
Notice iconographique issue de Wikimedia Commons. Titre: Romaine Lacaux. This painting may be Renoir's earliest signed canvas. Its sensitive display of color and light communicates an ideal of delicate, youthful beauty. The luminous tones of the background drapery and of the child's white blouse result from the artist's careful observation of reflected light and color on translucent materials. The delicate nuances of color, particularly in the young girl's face, reveal Renoir's previous training as a decorator of porcelain. He painted this portrait, commissioned by the vacationing Lacaux family, during his stay at an artist's colony in the village of Barbizon, near Paris.
Droits : Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; Peintures